Agriculture Liberalization and Marginalized Young Local People: Evidence from a Food Plantation in Lampung - Vanda Ningrum (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Since the 1980s, Indonesia has integrated its economy with global capitalism and has become liberal, particularly in the essential commodities, such as food, forestry, and mining. Moreover, this liberalization has created a diverse workforce and changed food production systems from family farming to corporate farming. Massive corporate farming raises a long debate, not only regarding the exclusion of small farmers but also regarding the changing social formations in the countryside that have led to a farmer regeneration crisis for young local people. Using social reproduction concepts, this study aims to analyze the rural social change including the impact for farmer families and access of local youth on job opportunity amid food corporate regime. The study is conducted in Terusan Nunyai sub-district of Central Lampung, which is identified as a high massive agriculture liberalization area in crops. The qualitative data is gathered from some literature reviews, direct observations, focus group discussion and in-depth interviews with some key informants. The research found that liberalization was followed by the land grabbing, and its food production systems have changed; they were previously based on household and tradition, but they switched into a corporate-based system (food estate). This corporate-based system employs many migrant workers, and after that, it changed the social class in the local community, between classes of employees and the local community classes as well. Limited capital and access of local people to get involved in the liberalization are considered to be the causes of marginalization of local people, including the young people's participation in the new social reproduction in the food regime.